Pengaruh Kualitas Produk Karang Hias (Coral) terhadap Peningkatan Penjualan di CV Bali Samudra Anugrah - Nurmulia Kaisal; Ratnawati Ratnawati; Mauli Kasmi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
The Influence of the Quality of Decorative Coral (Coral) Products in Increasing Sales at CV Bali Samudra Anugrah. Supervised by Ratnawati and Mauli Kasmi.A very important factor for a company in carrying out purchasing and sales transactions is quality. Quality is one of the attractions or desires of consumers. In developing products, companies have a greater opportunity to gain new customers, of course if the products sold meet expectations. The purpose of this research is to determine the influence, relationship or correlation, magnitude of perception, and significance of the quality of decorative coral (Coral) products on increasing sales at CV Bali Samudra Anugrah. The data collection technique used is a questionnaire. The data analysis technique is quantitative using validity tests, reliability tests, classical assumption tests, simple linear regression analysis and hypothesis testing.